MicroRNA response of inhalation exposure to hexanal in lung tissues from Fischer 344 rats. Issue 12 (24th September 2015) - Cho, Yoon; Song, Mi‐Kyung; Jeong, Seung‐Chan; Lee, Kyuhong; Heo, Yongju; Kim, Tae Sung; Ryu, Jae‐Chun
ABSTRACT: In previous studies, we have investigated the relationships between environmental chemicals and health risk based on omics analysis and identified significant biomarkers. Our current findings indicate that hexanal may be an important toxicant of the pulmonary system in epigenetic insights. MicroRNA (miRNA) is an important indicator of biomedical risk assessment and target identification. Hexanal is highly detectable in the exhaled breath of patients with chronic obstructive pulmonary disease (COPD) and chronic inflammatory lung disease. In this study, we aimed to identify hexanal‐characterized miRNA‐mRNA correlations involved in lung toxicity. Microarray analysis identified 56 miRNAs that commonly changed their expression more than 1.3‐fold in three doses (600, 1000, and 1500 ppm) within hexanal‐exposed Fischer 344 rats by inhalation, and 226 genes were predicted to be target genes of miRNAs through TargetScan analysis. By integrating analyses of miRNA and mRNA expression profiles, we identified one anti‐correlated target gene ( Chga ; chromogranin A; parathyroid secretory protein 1). Comparative toxicogenomics database (CTD) analysis of this gene showed that Chga is involved with several disease categories such as cancer, respiratory tract disease, nervous system disease, and cardiovascular disease. Further research is necessary to elucidate the mechanisms of hexanal‐responsive toxicologic pathways at the molecular level. This study concludes that our integrated approach to miRNA and mRNA enables us to identify molecular events in disease development induced by hexanal in an in vivo rat model. © 2015 Wiley Periodicals, Inc. Environ Toxicol 31: 1909–1921, 2016.